The effects of internet self-health management on patients with chronic disease multimorbidity: a 4-year longitudinal study - Wang, Yuyang; Hu, Qiang; Chen, Botian; Ma, Defu (Frontiers in Digital Health, 2025)
BackgroundThe escalating global burden of chronic diseases has given rise to a growing population affected by multimorbidity, defined as the co-occurrence of two or more chronic conditions. This health phenomenon is exacerbating disease burden through compounded clinical complications and increased healthcare demands. This study evaluates the effectiveness of internet-based self-health management in improving health behaviors and clinical indicators in patients with multimorbidity.MethodsA total of 30,745 adults aged ≥18 years from five northwestern Chinese provinces were enrolled. Following baseline data collection in 2013, participants received structured online health guidance covering diet nutrition, physical activity, and mental well-being. A follow-up assessment was conducted in 2017, involving questionnaire surveys and clinical measurements. Changes in health behaviors and clinical indicators of 2,535 patients with multimorbidity were analyzed. Binary logistic regression models were employed to identify factors influencing multimorbidity management outcomes.ResultsThe prevalence of multimorbidity at baseline in this study was 7.9%. After four years of health management, significant improvements were observed: smoking cessation rates increased from 8.2% to 10.2%, while low physical activity decreased from 29.0% to 24.6%. Both healthy individuals and multimorbid patients showed an increase in soybeans and nuts intake from 2013 to 2017. The fasting plasma glucose of the multimorbidity subjects decreased from 9.33 mmol/L in 2013 to 8.28 mmol/L in 2017, and the total cholesterol level decreased from 6.97 mmol/L to 6.26 mmol/L (P < 0.001). Significant reductions were also observed in triglycerides and low-density lipoprotein cholesterol levels (P < 0.001). The binary logistic regression results showed that being 40 years or older, male, having a family history of chronic diseases, changes in smoking status and sleep quality under health management guidance were influencing factors for effective control of multimorbidity.ConclusionInternet-based self-health management effectively improves health behaviors and clinical indicators in patients with chronic disease multimorbidity.